2018
DOI: 10.1021/acsanm.8b01992
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Thermal Conductivity in Polymer Nanocomposites via Covalent Functionalization of Boron Nitride Nanotubes with Short Polyethylene Chains for Heat-Transfer Applications

Abstract: Boron nitride, which possesses high thermal conductivity, is often incorporated into polymer matrixes for thermal management. The enhancement in the thermal conductivity depends on the filler shape, size, effective dispersion in the matrix, and interfacial thermal resistance between the filler and matrix, and the last two are the most challenging issues. To address these challenges, in this study two different covalent functionalization approaches on boron nitride nanotubes (BNNTs) with short polyethylene (PE)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(31 citation statements)
references
References 75 publications
1
30
0
Order By: Relevance
“…As shown in Figure 8(b), this value is higher than that of most thermal‐conductive composites at a comparable amount of the fillers such as the carbon nanofiber reinforced polyethylene (CNF/PE), 37 graphene nanoplatelets filled polyethylene (GNPs/PE), 38 expanded graphite (EG/PE), 39 multilayer graphene enhanced silicone rubber (Fe 3 O 4 /MG/SR), 40 and so on 40–42 . It is even comparable to the thermal‐conductive composites made from high‐content Al 2 O 3 , 43 or BN 44,45 fillers. It suggested that the large size of dispersed graphene nanosheets are important for thermal conductive polymer composites.…”
Section: Resultsmentioning
confidence: 97%
“…As shown in Figure 8(b), this value is higher than that of most thermal‐conductive composites at a comparable amount of the fillers such as the carbon nanofiber reinforced polyethylene (CNF/PE), 37 graphene nanoplatelets filled polyethylene (GNPs/PE), 38 expanded graphite (EG/PE), 39 multilayer graphene enhanced silicone rubber (Fe 3 O 4 /MG/SR), 40 and so on 40–42 . It is even comparable to the thermal‐conductive composites made from high‐content Al 2 O 3 , 43 or BN 44,45 fillers. It suggested that the large size of dispersed graphene nanosheets are important for thermal conductive polymer composites.…”
Section: Resultsmentioning
confidence: 97%
“…When the addition amount of the modified AlN was 25 wt%, the in-plane TC of the composite film reached 5.11 W m −1 K −1 . Quiles-Díaz et al [69] utilized two different covalent functionalization approaches on boron nitride nanotubes (BNNTs) with short polyethylene chain (Figure 2): Williamson reaction and Nitrene [1 + 2] chemistry. The filler had excellent compatibility with the high-density polyethylene matrix while maintaining the integrity of the nanotube.…”
Section: Covalent Bond Modificationmentioning
confidence: 99%
“…Hydroxylated BNNT (BNNT-OH) is reacted with a bromine-terminated polyethylene (PE-Br); reaction of pristine BNNT and azide-terminated polyethylene (PE-N3). Reproduced with permission [69]. Copyright 2019, American Chemical Society.…”
mentioning
confidence: 99%
“…12,[20][21][22] Particularly, signicant improvement in thermal conductivity was obtained for BNNT-based composites prepared by vacuum ltration of aqueous dispersions of nanotube/polymer mixtures. [22][23][24] However, ber spinning and mechanical property enhancement of BNNT assemblies remain to be challenging.…”
Section: Introductionmentioning
confidence: 99%